Pengaruh Persepsi Pemilik, Tingkat Pendidikan Pemilik, Dan Pengetahuan Akuntansi Pelaku Usaha Mikro Kecil Dan Menengah Terhadap Penggunaan Informasi Akuntansi (Studi Kasus UMKM Kecamatan Ledo Dan Kecamatan Lumar). - B1031141009, EVA KUMALA SARI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACThis study aims to analyze and obtain empirical evidence about the use of accounting information. The research hypothesis is the owner's perception, owner's education level, and owner's accounting knowledge of the use of accounting information. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. The research samples were 135 MSMEs in Ledo District and Lumar District, Bengkayang Regency. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. The method of determining the sample using purposive sampling. The data analysis method used is multiple regression techniques with the help of SPSS version 24. The results of this study indicate that: (1) there is a positive influence on the owner's perception of the use of accounting information. (2) there is a positive influence on the level of education of the owner towards the use of accounting information. (3) there is a positive influence on the accounting knowledge of the perpetrators of the use of accounting information. (4) there is a positive influence on the owner's perception, owner's education level, and accounting knowledge on the use of accounting information.Keywords: Owner Perception, Owner Education Level, Accounting Knowledge, Use of Accounting Information.